Optimization of Titanium Dioxide Nanoparticles in Mesoporous Electron Transport Layer Perovskite Solar Cell (Jurnal Elektronika dan Telekomunikasi, 2020)
Research about mesoporous TiO2 as an electron transport layer in perovskite solar cell has been done to obtain the best fabricated cell’s performance. In this research, the concentrations of opaque and transparent TiO2 nanoparticle were varied, in order to optimize the TiO2 mesoporous electron transport layer in FTO/CL-TiO2/MS-TiO2/Perovskite/P3HT/Ag perovskite-based solar cell. Morphological, optical, and electrical characteristics of TiO2 layers were investigated using scanning electron microscopy (SEM), four-point probe (FPP), and UV-Vis spectroscopy. The influences of those characteristics in solar cell performance were analyzed by using illumination of sun simulator with a light intensity of 500 W/m2. The results showed that transparent TiO2 has a higher conductivity and transmittance compared to the opaque TiO2. The concentration of TiO2 solutionin1:17 ratio resulted in higher electrical performance in both the transparent and opaque TiO2 layer. The best perovskite solar cell performance with PCE of 0.37% was achieved from the sample using TiO2 transparent layer with a concentration of 1:7 ratio.